2013
DOI: 10.1186/2050-7283-1-18
|View full text |Cite
|
Sign up to set email alerts
|

Are women better than men at multi-tasking?

Abstract: Background: There seems to be a common belief that women are better in multi-tasking than men, but there is practically no scientific research on this topic. Here, we tested whether women have better multi-tasking skills than men. Methods: In Experiment 1, we compared performance of 120 women and 120 men in a computer-based task-switching paradigm. In Experiment 2, we compared a different group of 47 women and 47 men on "paper-and-pencil" multi-tasking tests. Results: In Experiment 1, both men and women perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
74
4
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(95 citation statements)
references
References 29 publications
5
74
4
1
Order By: Relevance
“…Also, observed in this study is that slightly fewer female students (48%) multitask compared to their male counterparts (52%). This may not necessarily mean that female students multitask less but may only be in the case of agreement with [33], who found that females do handle multitasking better than males.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Also, observed in this study is that slightly fewer female students (48%) multitask compared to their male counterparts (52%). This may not necessarily mean that female students multitask less but may only be in the case of agreement with [33], who found that females do handle multitasking better than males.…”
Section: Discussionsupporting
confidence: 50%
“…An important conclusion from the study was that females would endorse greater frequency of texting compared to males. Indeed, [33]found that females do handle multitasking better than males. Also, [34] found that females were more susceptible to multitask compared to males and the female that engage in multitasking are more likely to have difficulties with academics [35].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Finally, some might point to the problem of the unequal gender ratio between VGPs and nVGPs. Although it is true that women are known to be better than men at task switching (e.g., Stoet, O'Connor, Conner, & Laws, 2013), we believe that the unbalanced gender ratio does not weaken our conclusions. Specifically, in our fullsample regression analyses, gender significantly predicted both switch and mixing costs, with men performing better than women on both types of costs.…”
Section: Discussionmentioning
confidence: 52%
“…Gender differences could be explained with different cognitive functioning of females and males. According to the previous research, women in general are much better in observing details than men, and also in multitasking -doing several things at the same time, while men in general having a tendency to focus on one task at the time, and be more aware while doing it (Stoet, O'Connor, Conner, & Laws, 2013).…”
Section: Discussionmentioning
confidence: 95%